Geographical linkage and trade disruption within global photovoltaic supply chains - Weilong Li; Meng Zhang; Mengyao Han (Geography and Sustainability)
Photovoltaics play an essential role in supporting the unprecedented growth of renewable energy transition as well as facing a series of trade risks due to complex international dynamics and intermittent trade disruptions. By combining complex network modeling and shock propagation analysis, the spatial-temporal evolution of photovoltaic supply chains worldwide was depicted, and the potential trade risks under different scenarios were elucidated in this study. The results show that the trade patterns of photovoltaic supply chains have evolved significantly, particularly characterized by the rise of China, Malaysia, Vietnam, and Thailand. The complexity of photovoltaic supply chains increases significantly with the addition of more nodes and edges in the networks. The vulnerability of critical photovoltaic supply chains tends to intensify with the increasing concentration of global supply chains in a geographic sense. The interruption of trade ties between China and Vietnam may lead to the most drastic impact on photovoltaic supply chains, followed by trade disruptions between Southeast Asia and North America. By unveiling the spatial-temporal network evolution and potential trade disruption of global photovoltaic supply chains, it is practical to propose rational and feasible strategies that consider the geographical diversification and international cooperation of photovoltaic supply chains worldwide.